Politicising documentary photography - Kuo, Li-Hsin (Javnost (Ljubljana), 2007)
This essay provides a contextualised account of social documentary photography in Taiwan during the second half of the 1980s and a critical review of Ren Jian magazine within a case study of Guan Xiao-rong's Dignity and Humiliation. The latter emerges as an exemplary documentary work on the socio-political issues of an ethnic group of indigenous Taiwanese. The essay suggests that Guan's mixed position of documentary photographer and campaign activist made his photographs a distinctive and rare humanistic contribution with a politicised dimension.
Keywords: Tajvan; politične razmere; družbene razmere; časniki; dokumentarna fotografija; fotografi; List of photographers